An experimental model for the study of craniofacial deformities - Costa,André de Mendonça (2010)
PURPOSE: To develop an experimental surgical model in rats for the study of craniofacial abnormalities. METHODS: Full thickness calvarial defects with 10x10-mm and 5x8-mm dimensions were created in 40 male NIS Wistar rats, body weight ranging from 320 to 420 g. The animals were equally divided into two groups. The periosteum was removed and dura mater was left intact. Animals were killed at 8 and 16 weeks postoperatively and cranial tissue samples were taken from the defects for histological analysis. RESULTS: Cranial defects remained open even after 16 weeks postoperatively. CONCLUSION: The experimental model with 5x8-mm defects in the parietal region with the removal of the periosteum and maintenance of the integrity of the dura mater are critical and might be used for the study of cranial bone defects in craniofacial abnormalities.